From Mars to Venus: Alteration of trust and reputation in online shopping - Pejvak Oghazi; Stefan Karlsson; Daniel Hellström; Rana Mostaghel; Setayesh Sattari (Journal of Innovation & Knowledge (JIK), 2021)
How customers develop purchase intentions in online shopping has been an area of recent interest. In this study, we ask whether males and females leverage trust into and perceived reputation of online retailers differently in reporting purchase intentions. Drawing on the literature on differences in males and females in online shopping behaviors, we propose that females rely on reputation in developing purchase intentions whereas males rely on perceived trust in developing purchase intentions. In a sample of 727 respondents in Sweden, we find support for the proposed associations. Implications for online retailers are discussed.
Keywords: 650; Gender; Online purchase; Online retail; Reputation; Trust